Climate Change Disproportionately Hits Women Farmers - Dawit, Mahilet; Mohammed, Yasin; Ambaw, Gebermedihin; Bekele, Tamrat; Abdella, Selam; Huyer, Sophia; Gondwe, Therese; Endrias, Abrhame; Amha, Yosef; Tesfaye, Abonesh; Auma, Joseph; Haile, Aynalem; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
▪ The effect of climate change is manifested by increased frequency, duration and intensity of extreme weather and climate events that include unexpected, unusual, severe, or unseasonal weather conditions. ▪ These primarily range from increases in seasonal temperature involving heat waves, dry spells, and water stress, as well as cold(frost) and changes in the precipitation patterns, including rainfall intensities and flush floods. ▪ The effects of extreme weather events are seen in rising economic (production) costs, loss of livestock (human) lives, droughts, floods, landslides, and salient changes in ago-ecosystems. ▪ These results in reduced crop yield, crop failure, reduced soil fertility, loss of vegetation cover, livestock number reduction and land degradation, among other factors. ▪ Women and men experience the impacts of climate change differently, but considering the existing gender inequalities, these climate crises pose more threats to women and young girls than men. ▪ Climate change is burdening women to provide energy, water and food for their families and livestock. ▪ Accordingly, the analysis indicated that women excessively suffer the impacts of climate disasters, as they are more exposed, sensitive and have low adaptive capacity.